2018
DOI: 10.3390/nu11010048
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coffee and Tea Consumption on Glucose Metabolism: A Systematic Review and Network Meta-Analysis

Abstract: Prospective cohort studies have described an association between coffee or tea consumption and the risk of developing diabetes. However, whether coffee or tea improves glucose metabolism remains uncertain. We investigated the effect of coffee and tea on glucose metabolism by conducting a systematic review and meta-analysis of randomized controlled trials. Electronic databases were searched for articles published up 19 February 2017. The primary endpoint was the mean difference in post-intervention fasting bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 61 publications
(104 reference statements)
4
32
0
Order By: Relevance
“…4,[22][23][24] Furthermore, Ikeda et al reported that the green tea extract inhibits pancreatic lipase and TG absorption in the intestines. 25) Hence, it could be postulated that pancreatic lipase and TG absorption were equally suppressed by polymerized and/or simple GTCs in kosen-cha. A network meta-analysis has reported that green tea consumption may decrease fasting blood glucose and showed its limited effects on 2 h postprandial glucose levels in 75 g OGTT and HOMA-IR.…”
Section: Discussionmentioning
confidence: 99%
“…4,[22][23][24] Furthermore, Ikeda et al reported that the green tea extract inhibits pancreatic lipase and TG absorption in the intestines. 25) Hence, it could be postulated that pancreatic lipase and TG absorption were equally suppressed by polymerized and/or simple GTCs in kosen-cha. A network meta-analysis has reported that green tea consumption may decrease fasting blood glucose and showed its limited effects on 2 h postprandial glucose levels in 75 g OGTT and HOMA-IR.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the effects of green tea catechin intake on postprandial glucose concentrations differ according to variations in catechin absorption and metabolism controlled by the circadian rhythm. In addition, other studies have reported that consecutive green tea ingestion has additive effects on health-related parameters, which could contribute to the prevention of obesity and diabetes [19,20]. However, no studies have examined the consecutive effects of the timing of green tea ingestion on glucose and insulin concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that it can prevent both dental caries and periodontal disease [10][11][12]. In addition to its beneficial effects on various health outcomes, such as all-cause mortality, cardiovascular disease, cancers, non-alcoholic fatty liver disease, metabolic syndrome, diabetes, and other health outcomes [13][14][15][16][17][18][19][20], green tea consumption is also considered to have an effect on oral health. In spite of abundant benefits from the basic sciences, there are relatively fewer clinical studies on the merit of green tea on oral health [21].…”
Section: Introductionmentioning
confidence: 99%